Raffaele Piria e gli studi sulla salicina - Zingales, Roberto (Chimica nella Scuola, 2025)
Raffaele Piria’s researches on salicin and populin are here reviewed to show: (1) how, at the middle of XIX century, the uncertainty on atomic weights led to different formulas for the same organic substance; (2) how the composition of large organic molecules could be found, by breaking them in smaller residuals; (3) how the attacking points, by which smaller molecules united each other to give bigger ones, were found.